From Challenges to Triumphs: Exploring the Role of Saudi Vision 2030 in Empowering Women Leadership in Education* - Tahir IQBAL; Shabir AHMAD (Communications of International Proceedings, 2024)
Women’s underrepresentation in business leadership roles has been a critical debate globally. The recent women's empowerment initiatives under Saudi Vision 2030 have created new opportunities and mitigated challenges for Saudi women aspiring to leadership roles. In this research, we investigate how Saudi women's challenges, achievements, and the prospects they navigate influence their success in attaining leadership roles. In addition, we explore the moderating influence of Saudi Vision 2030 on these factors. Employing a quantitative approach, we conducted a survey involving 484 Saudi women working in the education sector across Saudi Arabia. The data was analyzed using SPSS and SmartPLS. The findings show that challenges, prospects, and achievements help Saudi women attain leadership success. In addition, Vision 2030 positively moderates these effects by mitigating challenges, enhancing prospects, and fostering achievements, thereby providing novel insights into the intricate dynamics of women's leadership in the Saudi context.
Keywords: Women Leadership; Saudi Vision 2030; Women Challenges; Women Achievements